2021
DOI: 10.20473/jphrecode.v5i1.23369
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Characteristics and Complementary Feeding for Children Under 2 Years Old: A Correlation Study in Tlatah Village, Purwosari, Bojonegoro

Abstract: Background: Complementary feeding (MPASI) is substitute meals for 6 months old child to meet nutritional needs that are no longer sufficient by exclusive breastfeeding. There are several  factors that can affect the delivery of MPASI by maternal namely, maternal age, level of education dan maternal occupation. Purpose: The purpose of this study is to find out the relationship between maternal age, education and occupation towards the provision of MPASI in children aged 0-2 years. Method: This research is a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The results of this study are in line with research conducted in Tlatah village, Purwosari, Bojonegoro, East Java, which shows that complementary feeding is not affected by the type of mother’s occupation (Savitri and Haqi, 2021). Contrary to this result, a study conducted by Yugistyowati and Marza (2017) showed that the mother’s occupation correlated with the complementary feeding practice.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are in line with research conducted in Tlatah village, Purwosari, Bojonegoro, East Java, which shows that complementary feeding is not affected by the type of mother’s occupation (Savitri and Haqi, 2021). Contrary to this result, a study conducted by Yugistyowati and Marza (2017) showed that the mother’s occupation correlated with the complementary feeding practice.…”
Section: Methodssupporting
confidence: 89%
“…The result stated that nonworking mothers had more free time and access to information regarding complementary feeding so there would be more nonworking mothers who practiced complementary feeding for their children. Working mothers seldom come to any counseling events organized by health workers; hence, they do not obtain information and knowledge about complementary feeding (Savitri and Haqi, 2021).…”
Section: Methodsmentioning
confidence: 99%